The evolution of wage inequality within local U.S. labor markets - Anthony Eisenbarth; Zhuo Fu Chen (Journal for Labour Market Research, 2022)
There are few concentrated studies on wage inequality across local labor markets at the city or metropolitan level. This paper studies the changes in wage inequality among 170 metropolitan areas by using micro-level data from the U.S. Census and American Community Survey from 1980 to 2019. We propose that shifts in the relative demand for "college-educated" or "college equivalent" workers have been persistent in both temporal and spatial dimensions; and that this persistence has contributed to the increase in wage inequality along with the rise in managerial employment. Using fixed-effects models, we find that on average, changes in managerial intensity between 1980 and 2019 accounts for 6.9% of the change in wage inequality across U.S. labor markets.
Keywords: B59; C33; J23; J31; 330; Wage inequality; Labor markets; Labor demand